2005
DOI: 10.18388/abp.2005_3466
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of enolase.

Abstract: Enolase (EC 4.2.1.11) is an enzyme of the glycolytic pathway catalyzing the dehydratation reaction of 2-phosphoglycerate. In vertebrates the enzyme exists in three isoforms: alpha, beta and gamma. The amino-acid and nucleotide sequences deposited in the GenBank and SwissProt databases were subjected to analysis using the following bioinformatic programs: ClustalX, GeneDoc, MEGA2 and S.I.F.T. (sort intolerant from tolerant). Phylogenetic trees of enolases created with the use of the MEGA2 program show evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…In general, the results were in good agreement with traditional taxonomy, with Ssc-eno and other arthropoda species clustered into a group within the phylum Arthropoda, then with other eukaryotic species, and finally prokaryotic species, such as protozoa and bacteria. In particular, enolases from vertebrates were characterized by greater intraspecific, rather than interspecies, similarities, demonstrated as separate monophyletic branches for three different enolase isoforms (α, β, and γ) reflecting their different functions; this results was consistent with previous study (Piast et al, 2005 ).…”
Section: Resultssupporting
confidence: 92%
“…In general, the results were in good agreement with traditional taxonomy, with Ssc-eno and other arthropoda species clustered into a group within the phylum Arthropoda, then with other eukaryotic species, and finally prokaryotic species, such as protozoa and bacteria. In particular, enolases from vertebrates were characterized by greater intraspecific, rather than interspecies, similarities, demonstrated as separate monophyletic branches for three different enolase isoforms (α, β, and γ) reflecting their different functions; this results was consistent with previous study (Piast et al, 2005 ).…”
Section: Resultssupporting
confidence: 92%
“…We also identified five underexpressed proteins in IBS (ENO1, transgelin, serpin peptidase inhibitor B5, alpha 1 cardiac muscle actin, and 40S ribosomal protein SA). ENO1 is a multifunctional enzyme that not only catalyzes the conversion of 2‐phosphoglycerate to phosphoenolpyruvate in the presence of Mg 2+ ions in glycolysis 60, but also plays a role in other processes such as growth control, hypoxic tolerance, and allergic responses, as well as bacterial and fungal infections, cancer, neurologic conditions, and autoimmunity 61.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, glycolytic enzyme enolase 1 (a-enolase, a homodimer of 47-48 kDa) was identified as an up-regulated protein. The enolase 1 enzyme catalyzes the conversion of 2-phosphoglycerate to phosphoenolopyruvate in the presence of Mg 21 ions [29], and plays a role in various processes such as growth control, hypoxic tolerance, and allergic responses, as well as several types of diseases, such as bacterial, fungal, cancer, neurologic, and autoimmunity [30]. It exists as a multienzyme complex with other glycolytic enzymes, such as pyruvate kinase, phosphoglycerate mutase, muscle creatine kinase, and aldolase, in the cytoplasm [31,32].…”
Section: Discussionmentioning
confidence: 99%